PENGARUH ANGKA MELEK HURUF DAN ANGKA HARAPAN HIDUP TERHADAP JUMLAH PENDUDUK MISKIN DI PROPINSI SUMATERA BARAT - Dores, Edi; Rosa, Yenni Del; Jolianis, Jolianis (Pendidikan Ekonomi, 2013)
ABSTRACTPoverty is a condition in which a person or family is unable to meet basic needs such as food, clothing, housing, education, and health. This study aimed to examine the effect of: (1) educational views of the literacy rate of the number of poor people, (2) health as seen from the amount of the life expectancy of the poor population and (3) the number of literacy rate and the number of digits life expectancy simultaneously to the number of poor people in the provinces of West Sumatra.The type of study is a quantitative and associative research, this study conducted in West Sumatra province. The data used in this study is a secondary data, the type of annual time series data from 2005 to 2011 were obtained from the BPS (Central Bureau of Statistics). The research variables are the number of poor is seen from the number of literacy rate and life expectancy the number of West Sumatra. The analysis model used is multiple linear regression analysis.Results of this study indicate that (1) literacy rate and a significant negative effect on the number of poor people in the provinces of West Sumatra, (sig = 0.004 <0.05) with the level of influence of -2.909 percent. (2) the life expectancy significantly and negatively related to the number of poor people in the provinces of West Sumatra, (Sig = 0.000 <0.05) with the level of influence of -4.353 percent (3) literacy rate and life expectancy significantly positive effect on the number of poor people in the provinces of West Sumatra together (sig = 0.000 <Î± = 0,05). Contribution together of independent variables to the dependent variable was used by 33.70 percent.